-12x+14=-11x+6-9x

Simple and best practice solution for -12x+14=-11x+6-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12x+14=-11x+6-9x equation:



-12x+14=-11x+6-9x
We move all terms to the left:
-12x+14-(-11x+6-9x)=0
We add all the numbers together, and all the variables
-12x-(-20x+6)+14=0
We get rid of parentheses
-12x+20x-6+14=0
We add all the numbers together, and all the variables
8x+8=0
We move all terms containing x to the left, all other terms to the right
8x=-8
x=-8/8
x=-1

See similar equations:

| -23+d=102 | | -63=f•9 | | 20+4p=6p | | 5.35x+182.90=$750 | | 3(x-4)+6=7x-9-5x | | 18x=8x-20 | | 13s-5=-11+12s | | 4x+9+6x-23+40=180 | | 79=7w+3(4w–1) | | Y=3.5x+22 | | 31x=45 | | –9+2z=–7z | | u/5-8=9 | | 15b=17+14b | | -5+3x+8=2x+9 | | 5x2/5=0 | | -11+17m=16m | | 7x-14-10=20x-8x | | +2y–18+8y=–2 | | x31=45 | | 20-14n=-12n-8 | | 3x+85=119 | | 4x+21=x-28 | | d−8=≥35 | | 8(p-6)=48 | | 11=35-a | | A(x)=(x)(150-2x) | | 2y–18+8y=–2 | | 1.8·(u÷1.8)=3.6 | | f/0.25*0.25=16*0.25 | | 2x+3+5=20 | | -(v+6)+2(4v+2)=45 |

Equations solver categories